On the development of a web extension for text authentication on google chrome - M. Nomani, Kabir; Tayan, Omar; Alginahi, Yasser M.; Md Munirul, Hasan; Rahman, Md. Arafatur (IEEE, 2019)
Web extension is a software that can be installed on a web browser. A web-extension link is displayed as an icon on the toolbar of the browser. Based on browsing activity, the extension works automatically or by clicking the extension icon depending on the functionalities made in the extension software. In this work, we developed a web extension on google chrome browser to verify online texts by simply clicking on an extension button. Upon clicking the button, the underlying algorithm in the extension software retrieves the texts from the current web-page being displayed. Verification and authentication of texts are performed by comparing the retrieved texts with text database. According to the comparison, texts are highlighted in colors. We consider authentication of Arabic Hadith texts for a case study. The authentic Hadith texts are highlighted by green color; authentic texts with partial diacritics, by yellow; and unauthentic texts, by red. This technique can also be used to authenticate laws, constitutions and Government documents.